2008
DOI: 10.1002/bit.22172
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Q‐PCR Based Approach to Measuring Endogenous Retroviral Clearance by Capture Protein A Chromatography

Abstract: Quantification of virus removal by the purification process during production is required for clinical use of biopharmaceuticals. The current validation approach for virus removal by chromatography steps typically involves time-consuming spiking experiments with expensive model viruses at bench scale. Here we propose a novel, alternative approach that can be applied in at least one instance: evaluating retroviral clearance by protein A chromatography. Our strategy uses a quantitative PCR (Q-PCR) assay that qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…(Zhang et al, 2009;2014 through but decreased during washes. The studies performed here do not directly demonstrate such direct association but it is the simplest mechanism consistent with the data.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…(Zhang et al, 2009;2014 through but decreased during washes. The studies performed here do not directly demonstrate such direct association but it is the simplest mechanism consistent with the data.…”
Section: Discussionmentioning
confidence: 93%
“…These methods have been used widely to study the separation of the product-and processrelated impurities Kelley et al, 2008;Sisodiya, Lequieu, Rodriguez, McDonald, & Lazzareschi, 2012;Wensel, Kelley, & Coffman, 2008). The limited application of HTS for virus clearance studies is likely due to the cost, complexity, and need for specialized labs, all of which can be overcome in scale-down protein A models using quantitative methods to measure CHO endogenous, noninfectious RVLP (M. Zhang et al, 2009Zhang et al, , 2014 | 847 hydrogen-bond, or combinations of these functional groups that reverse the effect. The limited application of HTS for virus clearance studies is likely due to the cost, complexity, and need for specialized labs, all of which can be overcome in scale-down protein A models using quantitative methods to measure CHO endogenous, noninfectious RVLP (M. Zhang et al, 2009Zhang et al, , 2014 | 847 hydrogen-bond, or combinations of these functional groups that reverse the effect.…”
Section: Introductionmentioning
confidence: 99%
“…For RVLP, the viral RNA was extracted using Qiagen EZ1 virus mini kit v2.0 with the EZ1/EZ1 advanced robotic system, according to vendor instructions. Free viral nucleic acids not associated with intact virus particles were removed based on the digestion procedures described earlier (Lute et al, ; Zhang et al, ) with slight modifications (10 μL DNase I, 40 μL of DNase I buffer, and 350 μL sample volume).…”
Section: Methodsmentioning
confidence: 99%
“…Such traditional full studies can be extremely expensive and time‐consuming to perform if using virus‐spiking to determine viral clearance capacity. Previous publications report comparable clearance when using QPCR assays that quantify either CHO endogenous retrovirus‐like particles (RVLP) or spiked X‐MuLV, and that retrovirus removal by Protein A could be evaluated by RVLP removal using samples from a Protein A process characterization studies (Zhang et al, ). In this report, we propose an experimentally determined QbD‐based approach for assessing viral clearance by Protein A chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…This was first reported in 2009 by M. Zhang of Genentech Inc. (6) and expanded upon at the 2011 Symposium by M. Zhang (Session IV). It was reported that RVLP removal by protein A chromatography is comparable to that measured from spiked MuLV, and that RVLP removal determination can use full-scale samples.…”
Section: Cho Rvlp Assay Implementationmentioning
confidence: 79%